2019
DOI: 10.1016/j.sigpro.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

FFT multichannel interpolation and application to image super-resolution

Abstract: This paper presents an innovative set of tools to support a methodology for the multichannel interpolation (MCI) of a discrete signal. It is shown that a bandlimited signal f can be exactly reconstructed from finite samples of g k (1 ≤ k ≤ M ) which are the responses of M linear systems with input f . The proposed interpolation can also be applied to approximate non-bandlimited signals. Quantitative error is analyzed to ensure its effectiveness in approximating non-bandlimited signals and its Hilbert transform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In an ideal interpolation, given the appropriate conditions, a continuous signal can be exactly reconstructed from the discrete points [CHE19]. A spatial interpolation can predict the values of the unknown points by processing the surrounding variables with meaningful values within the same region.…”
Section: Fundamental Concepts Of Data Interpolationmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ideal interpolation, given the appropriate conditions, a continuous signal can be exactly reconstructed from the discrete points [CHE19]. A spatial interpolation can predict the values of the unknown points by processing the surrounding variables with meaningful values within the same region.…”
Section: Fundamental Concepts Of Data Interpolationmentioning
confidence: 99%
“…By means of the interpolation technique it is possible to reconstruct or approximate the continuous signals from a series of discrete points [CHE19]. This technique has been widely applied to super-resolution and im-1 age reconstruction in ultrasonic tomography [DON16] [FAN17] [FAN18].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have been given to the sampling theorems for the periodic bandlimited functions [10,11]. Moreover, the multichannel sampling approach has been extended to the time-limited functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…And the matrix involved in this inverse problem may have a large condition number if the sample sets {g m ( 2πp L ), 0 ≤ p ≤ L − 1}, 1 ≤ m ≤ M have a high degree of relevance. In spite of this, in [8,12], the authors showed that the large scale (N s ) inverse problem could be converted to a simple inversion problem of small matrices (M × M ) by partitioning the frequency band into small pieces. Moreover, the closed-form of the MCI formula as well as the FFT-based implementation algorithm (see Algorithm 1) were provided.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above difficulty, the low resolution images are first upsampled. Then, the upsampled images are processed via the lowpass interpolation filters [5]. Since the upsampling operation and the lowpass filtering are the linear operators, the obtained performances are limited by these linear operators.…”
Section: Introductionmentioning
confidence: 99%